Socio-cultural drivers of waste management practices: a KAP-based systematic review with lessons from Dhaka and diverse urban contexts - Roy, Nirmal; Abd Manaf, Latifah; Mohammad Ramli, Abu Hanifah (Elsevier, 2025)
Rapid urbanisation and population growth in Dhaka have exacerbated the challenges of municipal solid waste (MSW) management. While technical solutions and policies exist, their effectiveness is frequently undermined by socio-cultural barriers that shape how communities perceive, engage with, and act on waste management initiatives. This study systematically analyses the socio-cultural factors influencing MSW management in Dhaka, guided by the Knowledge, Attitudes, and Practices (KAP) framework, and compares these with international experiences to identify strategies for sustainable and inclusive waste management. Following PRISMA guidelines, peer-reviewed articles were systematically collected, screened, and synthesised. The review categorised findings into major factors and sub-factors, drawing on evidence from diverse geographic contexts to highlight parallels and contrasts with Dhaka. The analysis shows that although awareness of sustainable waste practices is relatively high, behavioural adoption remains constrained by cultural stigma, insufficient infrastructure, gender-based exclusion from decision-making, and the inadequate integration of grassroots workers, particularly women and informal waste collectors and recyclers who operate outside the formal system. Comparative evidence from other countries proves that targeted education, incentives, community leadership, and inclusive infrastructure significantly advance participation and waste segregation. Strengthening Dhaka's waste management requires interventions beyond technology and regulation, embedding behavioural transformation strategies into policy and practice. Culturally tailored awareness campaigns, gender-inclusive programmes, and multi-stakeholder engagement are important to build public trust, enhance participation, and accomplish the city's sustainability goals.